TNF-α/IL-10 Ratio Correlates with Burn Severity and May Serve as a Risk Predictor of Increased Susceptibility to Infections - Tsurumi, Amy; Que, Yok-Ai; Ryan, Colleen M.; Tompkins, Ronald G.; Rahme, Laurence G. (Frontiers in Public Health, 2016)
Severe burn injury renders patients susceptible to multiple infection episodes, however identifying specific patient groups at high risk remains challenging. Burn-induced inflammatory response dramatically modifies the levels of various cytokines. Whether these changes could predict susceptibility to infections remains unknown. The aim of this study was to determine the early changes in the pro- to anti-inflammatory cytokine ratio and investigate its ability to predict susceptibility to repeated infections after severe burn trauma. The patient population consisted of 34 adult patients having early (≤48 hours since injury) blood draws following severe (≥20% total burn surface area (TBSA)) burn injury, and suffering from a first infection episode at least one day after blood collection. Plasma TNF-α and IL-10 levels were measured to explore the association between the TNF-α/IL-10 ratio, hypersusceptibility to infections, burn size (TBSA), and common severity scores (Acute Physiology and Chronic Health Evaluation (APACHEII), Baux, modified Baux (R-Baux), Ryan Score, Abbreviated Burn Severity Index (ABSI)). TNF-α/IL10 plasma ratio measured shortly after burn trauma was inversely correlated with burn size and the injury severity scores investigated, and was predictive of repeated infections (≥3 infection episodes) outcome (AUROC [95%CI] of 0.80 [0.63–0.93]). Early measures of circulating TNF-α/IL10 ratio may be a previously unidentified biomarker associated with burn injury severity and predictive of the risk of hypersusceptibility to repeated infections.